Internet connectivity disruption in Zimbabwe (Zimbabwe) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Zimbabwe. Data sourced from IODA.
Network Disruption Incident ID: ZW-2026-0048. Severity: critical. Confidence: 67%